Violencia de género y la estabilidad emocional en las mujeres del rcto. San Francisco de Chipe - Caisa Velez, Cristina Josselyn (2019)
El objetivo del presente trabajo de investigación fue demostrar la afectación de la violencia de género en la estabilidad emocional de las mujeres del Rcto San Francisco de Chipe, por lo que se ha convertido en un enfoque cuantitativo de diseño experimental y de corte transversal descriptivo. Se trata de una muestra compuesta por mujeres maltratadas en el Recinto San Francisco de Chipe cantón La Maná, provincia de Cotopaxi, dando a conocer los resultados que existe un nivel de dependencia emocional alto en la muestra de estudio. he people who are part of the research were 80 women which is a sample taken for the execution of this investigative process. The information obtained was collected through a data collection form and two survey questionnaires duly validated by professionals in the area of Clinical Psychology; which are intended to measure: the one, links related to the choice of partner and the other, related to determine emotional instability features based specifically on basic emotions that are present in individuals in addition to assessing the level and predominance in which find the same. According to the present work, the respondents maintain different levels of Emotional Instability that fluctuate between moderate to severe and in a greater percentage of the population investigated an adequate choice of couple. For this as a proposal, a psychotherapeutic intervention scheme was developed based on the Rational-Emotive Model, which aims to decrease the development of assertive thoughts and emotions that encourage an adequate choice of partner, using therapeutic techniques and strategies, all These phases worked on the most outstanding features identified at a general level.